The effect of online training based on stroke educational program on patient’s quality of life and caregiver’s care burden: a randomized controlled trial - Amir Mohamad Nazari; Abbas Abbaszadeh; Rouzbeh Kazemi; Vahid Yousofvand; Mitra Zandi (BMC Nursing)
Abstract Background Stroke is considered one of the leading causes of both mortality and morbidity on a global scale. The significant impact on the health and quality of life of stroke survivors and their caregivers is well-acknowledged due to the stressful consequences of dependency and the need for home care. This study aims to examine the impact of online training utilizing a stroke educational program on the patient’s quality of life and their caregivers’ care burden. Materials and methods From March to August 2024, a randomized, controlled trial was conducted. In this study, a total of 60 dyads consisting of stroke patients and their caregivers participated. Participants were selected by convenient sampling method and then randomly allocated into intervention and control groups using research randomizer software. The participants in the intervention group received the educational content through the WhatsApp application during a series of fifteen sessions, each lasting between 45 and 60 min. The control group was given standard hospital education. The data collection and analysis process entailed the utilization of questionnaires, which encompassed demographics, the Stroke Specific Quality of Life Scale (SS-QOL), and the Zarit burden of care questionnaires. Results In the intervention group, the average age of patients and caregivers was 60.23 ± 12.41 and 51.56 ± 10.42, respectively, while in the control group, it was 61.73 ± 12.61 and 53.60 ± 9.03, respectively. The intervention group demonstrated a statistically significant difference in the mean score of patient’s quality of life, comparing the baseline with the post-intervention periods (134.73 ± 33.51 vs. 90.56 ± 6.51 and 130.46 ± 30.67 vs. 90.56 ± 6.51; p < 0.05). Furthermore, a statistically significant difference in the mean score of caregiver’s care burden was noted between the baseline and post-intervention periods (80.23 ± 7.99 vs. 65.43 ± 16.52 and 80.23 ± 7.99 vs. 60.53 ± 21.34; p < 0.05). Conclusion The implementation of an online training program focused on stroke education, resulted in an improvement in the quality of life for stroke patients, as well as a reduction in the care burden for their caregivers. As a result, it is essential to provide education to patients and their caregivers to improve patient care and minimize stroke complications. Trial registration IRCT20240609062065N1, 2024/08/31.